Impactos hidrológicos decorrentes de diferentes cenários de cobertura do solo e mudanças climáticas em uma bacia hidrográfica da Serra da Mantiqueira, utilizando o modelo DHSVM - Alvarenga, Lívia Alves (2015)
Human interference in the climate system and land cover in watersheds has presented risks to natural balance. As such studies on the potential impacts on the water cycle due to land cover changes as well as climate change stand out. This study was conducted in the Lavrinha Watershed (LW), located in the Serra da Mantiqueira range, Minas Gerais. Using the hydrological model "Distributed Hydrology Soil Vegetation Model" (DHSVM), hydrological processes have been simulated. Initially, calibration and validation of the DHSVM with four years of data (2006-2010) was carried out. Thus, the effects of possible hydrological changes due to land cover changes were assessed using five different scenarios in the LW. The comparison of different land cover scenarios showed that deforestation in the Atlantic Forest can lead to monthly changes in hydrological processes, such as increased soil moisture, overland flow, total runoff and streamflow, and a decrease of water intercepted by the canopy, evapotranspiration and water table depth. In this work, the hydrological response of the LW was also compared using different soil class maps. Soil maps were used obtained based on pedological survey and the HAND model. When compared to simulations made with the soil maps obtained from pedological survey, the simulations based on soil maps obtained by the HAND model showed small variations in the simulated of streamflow and overland flow values and also of the distributed hydrological variables. This research also analyzed the simulated hydrological components for different width scenarios of riparian vegetation. The results showed that the riparian vegetation plays an important role in the groundwater recharge under the LW conditions. However, the average annual streamflow showed a decrease with increasing riparian vegetation in the area studied. These results can be mainly explained by the increase in average daily evapotranspiration and interception of precipitation and average daily reduction of overland flow. Finally, the hydrological impacts associated with climate change were also assessed in this study. Climate changes projected by the regional climate model Eta-CPTEC/INPE coupled to the Global Circulation Model HadGEM2-ES, for the RCP 8.5 future scenario indicated decreased rainfall concentration and the increase in air temperature in the region studied. Thus, future monthly streamflow projections simulated by DHSVM over the twenty-first century showed a decrease between 20 and 77% in the LW.